Pengembangan Modul Ajar Bahasa Indonesia Siswa Disleksia Kelas X di Sekolah Inklusi - Sohnui, Suhailee; Mukhlis, Muhammad; Asnawi, Asnawi; Yuliawan, Tri; Alber, Alber; Shafina, Vira (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This research is motivated by the lack of Indonesian language teaching modules specifically designed for students with dyslexia in inclusive schools. The study aims to design an effective teaching module that aligns with the learning characteristics of dyslexic students. It employs the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. However, this research was limited to the first three stages analysis, design, and development. The analysis stage involved identifying the needs and challenges faced by dyslexic students through interviews and observations. The design stage focused on creating the module based on analysis results and a review of effective learning methods. In the development stage, learning content was created using a multisensory approach and educational technology integration. The resulting module was developed by adapting the materials, methods, and media to be simpler, more interactive, and supportive of multisensory learning styles. Expert validation produced an Aiken’s V score of 0.85, indicating high validity and confirming that the module is suitable for use. This teaching module is considered effective in supporting inclusive education and serves as an innovative alternative to improve literacy skills among dyslexic students.